RIWAYAT PERADABAN AWAL ISLAM MINANGKABAU DI NAGARI TAPAKIS ULAKAN KABUPATEN PADANG PARIAMAN - Mhd Nur (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2022)
Nagari Tapakis is located in Ulakan Tapakis District, Padang Pariaman Regency. The position of this nagari is on the west coast of West Sumatra facing the Indian Ocean. The purpose of this study is to reveal and explain the first entry of Islam in Nagari Tapakis which was developed by Sheikh Madinanh. Then continued by his student Sheikh Burhanuddin by developing Islam in Ulakan. The method used in this research is the historical method, which consists of heuristics, criticism, interpretation, and historiography stages. Sheikh Medina and Sheikh Burhanuddin have changed the civilization of ignorance in Tapakis into an Islamic civilization. They further developed the religion of Islam in the Minangkabau darek area. The nuances of the economic life of the Tapakis community after embracing Islam changed and they still depend on the sea. The world of agriculture is still dominant because the land is fertile. Pre-Islamic socio-religious conditions in Tapakis became unstable when Islam entered. Several surau were built and spread in Tapakis District as Islamic educational institutions. Many of the community members who initially worked as fishermen and active farmers also studied Islam, because it was easy to learn Islam. Many parents gave their children to Sheikh Burhanuddin to be educated in Islam